Selection of Acetic Acid Bacterial Strains and Vinegar Production From Local Maltese Food Sources - Mizzi, Joseph; Gaggìa, Francesca; Bozzi Cionci, Nicole; Di Gioia, Diana; Attard, Everaldo (Frontiers in Microbiology, 2022)
This study investigates the isolation, identification, and fermentation performance of autochthonous acetic acid bacteria (AAB) from local niche habitats on the Island of Gozo (Malta) and their further use for vinegar production, employing local raw materials. The bacteria were isolated from grapevine berries and vinegar produced in the cottage industry. Following phenotype and genotype identification, the AAB were ascribed to the genera Acetobacter, Gluconobacter, and Komagataeibacter. A mixture of selected AAB was tested as an inoculum for vinegar production in bench fermenters, under different conditions and substrates, namely, grapes, honey, figs, onions, prickly pear, and tomatoes. The bench fermenters were operated under semi-continuous fermentation where working volumes were maintained by discharging and subsequent recharging accordingly to maintain the acidity in fermenters by adding 30–50 g/l of acetic acid for optimal Acetobacteraceae performance. Finally, the vinegar products obtained from the different substrates were evaluated for their quality, including organoleptic properties, which showed the superior quality of wood-treated vinegar samples with respect to neat vinegar samples.